Decapod crustacean larvae dynamics in the west continental coast of Portugal: the region adjacent to Aveiro coastal lagoon as model - Bartilotti, Cátia Alexandra Vieira (2014)
Tese de dout., Ciências do Mar, Faculdade de Ciências do Mar e do Ambiente, Univ. do Algarve, 2010